Lexico-Semantic Properties of Literature Positive Assessment Units - Usmonova Zamira Uralovna; Semenova Marina Albertovna (Genius Journals, 2022)
The article provides an analysis of words that express a positive assessment. Words that express a positive assessment are illustrated with examples and their lexical and semantic aspects are explained in detail. Theoretical opinions of scientists are quoted and commented on.
Keywords: Evaluation; attitude; order of speech; poetics